BLEOMYCIN-INDUCED REVERSIBLE ACUTE INTERSTITIAL PNEUMONIA - O, Balaji; Amita d,; Patil, Navin; Thomas, Joseph (Asian Journal of Pharmaceutical and Clinical Research, 2017)
As of now, about 380 medications are implicated in causing respiratory reactions and most common among that is drug-induced interstitial disease. Oral, parental as well inhalational drugs are known to cause drug-induced interstitial lung disease. Bleomycin is a chemotherapeutic agent used in the treatment of lymphomas, germ cell tumors of the testes. Most common pulmonary toxicity is diffuse alveolar damage with nonspecific interstitial pneumonitis being next. We report a case of bleomycin-induced reversible acute interstitial pneumonia in a Hodgkin's lymphoma patient with adriamycin, bleomycin, vinblastine, dacarbazine regimen. Causality assessment was done using Naranjo scale, and probable causal relationship was established. Adverse drug reaction was found to be moderately severe and not preventable as per Hartwig's severity and Thornton's preventability scaling respectively. Â 